PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. POS INDONESIA (PERSERO) KANTOR POS BANJARMASIN 70000 - Mailiana -; Penta Lestarini B; Raudhatul Jannah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research aimed to know the influence environment of work and communication to performance employee at PT. POS (Persero) post office 70000 Banjarmasin. The method used descriftive qualitative methods, namely measurement of objective statistical data and trough SPSS version 16. The Result found that the t-test the environment of work variabels by 4,442 bigger than t table is 1,667 which means a significant effect on performance employee at PT. POS (Persero) post office 70000 Banjarmasin Communications variabel shows the t-count equal to 3, 251 is bigger than t- table is 1,667 which means a significant effect on performance employee at PT. POS (Persero) post office 70000 Banjarmasin F–test result shows F count of is 26,591 greater than F-table is 3,938.